2013
DOI: 10.1103/physrevb.87.220404
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of ferromagnetism and Jahn-Teller distortion in LaMn1xCrxO3

Abstract: The emergence of a ferromagnetic component in LaM nO3 with low Cr-for-Mn substitution has been studied by x-ray absorption spectroscopy and x-ray magnetic circular dichroism at the Mn and Cr K edges. The local magnetic moment strength for the Mn and Cr are proportional to each other and follows the macroscopic magnetization. The net ferromagnetic components of Cr 3+ and M n 3+ are found antiferromagnetically coupled. Unlike hole doping by La site substitution, the inclusion of Cr 3+ ions up to x = 0.15 does no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…In fact, it is in line with a previous report [15]. The DE mechanism between Mn 3+ ion and Cr 3+ ion has been suggested to be possible occurs in this study due to the Cr 3+ ion may have a similar role with Mn 4+ where the Cr 3+ (t 3 2ge 0 g) ion have same electronic configuration with Mn 4+ (t 3 2ge 0 g) ion [15,20]. Apart from that, the increasing of Cr content also influenced the intensity of the resistivity where this can be suggested to be due to the increase of carrier concentration as result of enhancement of the DE mechanism [15].…”
Section: Methodssupporting
confidence: 93%
“…In fact, it is in line with a previous report [15]. The DE mechanism between Mn 3+ ion and Cr 3+ ion has been suggested to be possible occurs in this study due to the Cr 3+ ion may have a similar role with Mn 4+ where the Cr 3+ (t 3 2ge 0 g) ion have same electronic configuration with Mn 4+ (t 3 2ge 0 g) ion [15,20]. Apart from that, the increasing of Cr content also influenced the intensity of the resistivity where this can be suggested to be due to the increase of carrier concentration as result of enhancement of the DE mechanism [15].…”
Section: Methodssupporting
confidence: 93%
“…Additionally, XMCD retains the chemical sensitivity of X-ray absorption spectroscopy (XAS), which is priceless when two or more TMs are present. Many kinds of compounds could thus be investigated and their properties better understood, for instance oxides (Subías et al, 2009;Ramos et al, 2009), alloys (Dartyge et al, 1995), magnetic multilayers (Pizzini et al, 1995), intermetallic compounds (Boada et al, 2010a), molecular magnets (Train et al, 2004) or Prussian blue analogs (PBAs) (Verdaguer et al, 1995(Verdaguer et al, , 1999Dujardin et al, 1998;Champion et al, 2001;Cafun et al, 2013;Lahiri et al, 2016). All these results were obtained thanks to worldwideavailable beamlines allowing for TM K-edge XMCD measurements, using either a scanning setup (Rogalev & Wilhelm, 2015;Haskel et al, 2007;Nakamura & Suzuki, 2013;Poldi et al, 2020) 1 or a dispersive one, for instance on ODE (Baudelet et al, 2011(Baudelet et al, , 2016 at SOLEIL (France), ID24 ISSN 1600-5775 (Mathon et al, 2004;Pascarelli et al, 2016) at ESRF, EDXAS (Cezar et al, 2010) at LNLS (Brazil), or BL-08 (Patra et al, 2019) at Indus-2 (India).…”
Section: Introductionmentioning
confidence: 99%
“…This model suggests real electron transfer from Mn 3+ (Co 3+ ) to Mn 4+ (Co 4+ ) while this mechanism is effective only for the mixedvalence systems. However, it was found that the ferromagnetic state can be stabilized in some compounds where manganese or cobalt ions are in 3+ or 4+ oxidation state only [3][4][5][6][7][8][9][10][11]. Orbitally disordered state in parent LaMnO 3 above 750 K results in dominant ferromagnetic interactions, as confirmed by the positive Weiss constant (θ ≈ 160 K [3,4]).…”
Section: Introductionmentioning
confidence: 95%
“…Orbital ordering leads to anisotropic superexchange interactions and Atype antiferromagnetic order below 140 K [3]. The longrange ferromagnetic component has been observed in the LaMn 1−x Ga x O 3 (0.2 < x < 0.6) and LaMn 1−x Cr x O 3 (0.4 < x < 0.6) series containing only Mn 3+ species [5][6][7][8][9][10][11]. These series show gradual transition into the orbitally disordered state upon substitution with Ga 3+ (x > 0.…”
Section: Introductionmentioning
confidence: 99%